Analisis respon peserta didik penggunaan media crossword puzzle keragaman budaya kelas IV SD Supriyadi 02 - Najichah, Aina; Subekti, Ervina Eka; Sofiati, Ranto Netty (Jurnal Pendidikan Dasar, 2024)
This research is motivated by field findings, where the author saw students' inactivity in learning. Based on this, the author applies learning using crossword puzzle media. This research includes qualitative descriptive research. Research techniques use interviews, observation and questionnaires. The subjects of this research were class IV students at SD Supriyadi 02 Semarang with a total of 28 students. This research aims to determine students' responses to the use of crossword puzzle media in class IV Pancasila Education subjects on Cultural Diversity in Indonesia, through 4 question indicators, namely students' feelings of happiness, interest, attention and participation. These four aspects were accumulated with a student response result of 94%, so it could be said that the student response to using the Crossword Puzzle media on Cultural Diversity in Indonesia class IV was in the very good category